2010
DOI: 10.1002/cbf.1642
|View full text |Cite
|
Sign up to set email alerts
|

Preventive role of PD‐1 on MPTP‐induced dopamine depletion in mice

Abstract: Many current studies of Parkinson's disease (PD) suggest that inflammation is involved in the neurodegenerative process. PD-1, a traditional Korean medicine, used to treat various brain diseases in Korea. This study was designed to investigate the effect of PD-1 extract in the Parkinson's model of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) lesioned mice. The MPTP administration caused the dopamine neuron loss in the striatum and substantia nigra pars compacta (SNpc), which was demonstrated by a deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…In our study, Bcl-2 staining intensity was found to be decreased in the MPTP-induced group. This result was consistent with previous studies [58,[80][81][82][83]. In the present study, administration of DHA increased Bcl-2 levels in MPTP-induced + DHA-treated dopaminergic neurons compared to the MPTP-induced group.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, Bcl-2 staining intensity was found to be decreased in the MPTP-induced group. This result was consistent with previous studies [58,[80][81][82][83]. In the present study, administration of DHA increased Bcl-2 levels in MPTP-induced + DHA-treated dopaminergic neurons compared to the MPTP-induced group.…”
Section: Discussionsupporting
confidence: 94%